Answer:
x + y : x - y = (5/2+1/2) : (5/2-1/2)
x + y : x - y = 3 : 2
Therefore, x + y : x - y= 3 : 2 is proved.
Explanation:
Given
x + y : x - y = 3 : 2
As
![x + y = 3](https://img.qammunity.org/2021/formulas/mathematics/high-school/jdif9go5bxk0tf1x7o4jqbbmsng6qm3164.png)
![x - y = 2](https://img.qammunity.org/2021/formulas/mathematics/high-school/f1ejsua79oyl4tqkyh1x6azbc84x9ljktd.png)
Solving to find x and y
![\begin{bmatrix}x+y=3\\ x-y=2\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/high-school/vqmnyft2e12jn2k8yi30dcysv369sew336.png)
![x-y=2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fnrdszlwbnrkhtdp3w7p4mda21tzqcnjt1.png)
![-](https://img.qammunity.org/2021/formulas/mathematics/high-school/1f0xq4ut585caaz76v535ydy2wlbnb2bfh.png)
![\underline{x+y=3}](https://img.qammunity.org/2021/formulas/mathematics/high-school/1tz28qvrszv2h1uex1efkwheyzqremhmt5.png)
![-2y=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/xx7og9ge21upiyxci1z3rsmn8n6sehw6de.png)
![\begin{bmatrix}x+y=3\\ -2y=-1\end{bmatrix}](https://img.qammunity.org/2021/formulas/mathematics/high-school/6atg4m6a9fg7krf2tchei7m5bm9okkgyob.png)
solve for y
![-2y=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/xx7og9ge21upiyxci1z3rsmn8n6sehw6de.png)
Divide both sides by 2
![(-2y)/(-2)=(-1)/(-2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5ku3gzf1uh4mseb4lff9g5zq0eiljjtr5r.png)
![y=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/9j8yddngb73shqwuo7n7xt4nwc808xmjqa.png)
![\mathrm{For\:}x+y=3\mathrm{\:plug\:in\:}y=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hg182sfnh8lsp541fht4jt3a31y7zslhlh.png)
![x+(1)/(2)=3](https://img.qammunity.org/2021/formulas/mathematics/high-school/w533h10n9r9112vsp7emzqyuxfexe111q0.png)
![x+(1)/(2)-(1)/(2)=3-(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/pitr7601lwvn9f1ea09ruokfvxo54f6i58.png)
![x=(5)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y4kvnbtdwpfjy0auamdzjq4kx48xpi6voy.png)
so
![x=(5)/(2),\:y=(1)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/evhk7o9l2u7emeeyqrmd2mzytsuzdsoyda.png)
Thus,
x + y : x - y = (5/2+1/2) : (5/2-1/2)
x + y : x - y = 3 : 2
Therefore, x + y : x - y= 3 : 2 is proved.